Pendampingan Penerapan Akuntansi Syariah pada Pelaku Usaha Mikro - Siti Lailatur Rohmah; Dadang Heru Jatmiko; Elok Faiqoh; Yoga Ari Pratama; Binti Nur Asiyah (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play a role as one of the main drivers of the Indonesian economy, including in Tulungagung Regency, East Java. Based on the latest data, there are around 139,386 MSMEs in Tulungagung, but only a small number have financial report recording in an orderly manner and in accordance with sharia principles. In fact, good financial records not only help business actors in separating business and personal finances, but also make it easier to calculate profits, as well as business zakat obligations if they have met the nisab. This study aims to describe the implementation of community service activities in the form of sharia accounting assistance to business actors in Kedungwaru District, Tulungagung. The method used is a participatory method with an observation, interview, and direct mentoring approach. The team consisted of four students who conducted a needs assessment, evaluated the conditions of initial financial records, provided simple training related to cash, assets, liabilities, and capital recording, and introduced the basic principles of sharia accounting, including business zakat obligations. The results of the activity showed that the business actors who were accompanied were able to understand the importance of simple financial records, began to separate business and personal finances, and were interested in learning more about the calculation of business zakat. In addition, there has been an increase in the awareness of business actors regarding the value of blessings in sharia-compliant financial management. In conclusion, this mentoring activity has succeeded in improving the understanding and basic skills of business actors related to sharia-based financial recording. In the future, similar activities need to be carried out on an ongoing basis with a more in-depth scope of material, including the use of sharia-based digital recording applications.